Field relevant doses of the fipronil affects gene expression in honey bees Apis mellifera - Astolfi, Aline [UNESP]; Kadri, Samir Moura [UNESP]; de Castro Lippi, Isabella Cristina [UNESP]; Mendes, Daniel Diego [UNESP]; Alonso, Diego Peres [UNESP]; Ribolla, Paulo Eduardo Martins [UNESP]; de Oliveira Orsi, Ricardo [UNESP] (Springer Nature, 2022)
We analyzed the changes in the gene expression of forage honey bees (Apis mellifera) exposed to fipronil field-relevant dose (2.5 ppb/bee) by 1 or 4 h. A reduction in the expression of nine genes was observed after 4 h of exposure, five of which are related to the digestive system: endoglucanase E-4, MSS11 transcription activator, inositol monophosphatase 2-X1 transcription variant, ATP-binding cassette G subfamily, and cuticular protein 28; one related to exoskeleton composition: cuticular protein 28; two related to vitamin E transport and antioxidant system: alpha-tocopherol transfer protein-like and transcript variant X3. LOC551765, LOC100578929, and LOC102656070 were downregulated; however, these genes have not yet been studied. The results indicate that the fipronil causes changes in the expression of genes related to physiological and morphological, metabolism, and behavior in A. mellifera honey bees.
Keywords: gene expression; honey bees; pesticides; physiological effects